2021
DOI: 10.3390/sym13091735
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Processes in a Superconducting Adiabatic Neuron with Non-Shunted Josephson Contacts

Abstract: We investigated the dynamic processes in a superconducting neuron based on Josephson contacts without resistive shunting (SC-neuron). Such a cell is a key element of perceptron-type neural networks that operate in both classical and quantum modes. The analysis of the obtained results allowed us to find the mode when the transfer characteristic of the element implements the “sigmoid” activation function. The numerical approach to the analysis of the equations of motion and the Monte Carlo method revealed the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Numerical analysis has shown that the activation functions for the quantum neuron, initialised in the basic states, takes a sigmoidal shape (black and red curves in Figure 3 ). This is in a good agreement with the classical regime of operation [ 46 ].…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Numerical analysis has shown that the activation functions for the quantum neuron, initialised in the basic states, takes a sigmoidal shape (black and red curves in Figure 3 ). This is in a good agreement with the classical regime of operation [ 46 ].…”
Section: Resultssupporting
confidence: 86%
“…A single-junction superconducting interferometer with normalized inductance l , a Josephson junction without resistive shunting (JJ), an additional inductance l a , and an output inductance l out (see Figure 1b ) are the basis of the quantum neuron. This circuit has been presented before as a classic superconducting neuron for an adiabatic perceptron [ 42 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations